Genetic improvement and related activities. Regional activities. Brazil - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1987)
Close collaboration between CIAT and Brazil continued during 1986. Germplasm development was conducted through evaluating the jointly developed crosses in Brazil, rather than selecting the fixed lines in CIAT prior to shipment to Brazil. By the end of 1986, those segregating populations were in the F4-F5 generations ready for adaptation trials in several states throughout the country. Results of these evaluations are included. (CIAT)